Assessing the not‐invented‐here syndrome: Development and validation of implicit and explicit measurements. (15th May 2017) - Antons, David; Declerck, Mathieu; Diener, Kathleen; Koch, Iring; Piller, Frank T.
Summary: The not‐invented‐here (NIH) syndrome has been called one of the largest obstacles in innovation management, preventing effective knowledge transfer between organizational units and individuals. NIH is defined as a negatively shaped attitude towards knowledge that has to cross a disciplinary, spatial, or organizational boundary, resulting in either its suboptimal utilization or its rejection. Our goal is to equip scholars with appropriate measurement instruments for the phenomenon. On the basis of 4 studies with 1, 238 subjects overall, we developed an implicit measure based on the implicit‐association test as well as an explicit (survey) measure of NIH, taking into account theoretical insights on attitude structure. We provide evidence for reliability as well as construct and criterion validity. We want to facilitate further research on NIH and knowledge transfer (a) by providing a better theoretical framework for NIH on the basis of the tripartite componential model of attitudes, (b) by demonstrating the application of association‐based implicit measures for management research, and (c) by providing a validated multidimensional survey scale to measure NIH explicitly. We also provide recommendations on how managers can utilize the NIH measurement instruments to investigate NIH and potential countermeasures in detail and they can test the behavioral outcomes postulated by previous research.